Extrato metanólico de raízes de Piper tuberculatum e piplartina: verificação de atividade alelopática para potencial aplicação em processos biotecnológicos - Menin, Martha (2020)
The search for new solutions for weed control is of great relevance, since different cultures are continually developing resistance to agrochemicals. With this focus, the allelopathic potential was evaluated, a process by which specialized metabolites positively or negatively influence the development of other living beings, the methanol extract from the roots of Piper tuberculatum and its pure substance, piplartine, in weeds, Bidens pilosa (“hairy beggarticks”) and Euphorbia heterophylla (“mexican fireplant”), through germination and growth bioassays. The bioassays were conducted in a BOD chamber under controlled conditions at 30 °C (day) and 25 °C (night) with 12 hours of photoperiod, for 7 days during the germination test and for 14 days during the growth test. For bioassays with P. tuberculatum extract concentrations of 200, 300, 400, 500 and 600 mg L-1 were used, and for piplartine 125, 250, 500 and 750 mg L-1. The growth of root and aerial part of seedlings was analyzed, in addition to the variables: Index of germination speed, Average germination speed, Average germination time, Percentage of germinated seeds and abnormal and dead seedlings. The results showed that the application of P. tuberculatum extract decreases the germination speed index and germination percentage of the test plants, and that piplartine influenced the growth of root and aerial part and Germination speed index, Average speed of germination. germination and germination percentage of B. pilosa. Growth bioassays showed a decrease in the aerial part of E. heterophylla with the addition of P. tuberculatum and the radicle for piplartine application. For B. pilosa there was a decrease in the growth of the two parts with both solutions. The percentage of abnormal and dead seeds and seedlings was also evaluated, and it was noticed that the highest percentage of these cases remained in the highest concentrations, which demonstrates how the extracts influenced the development and survival of the target plants. Through these results it can be inferred that the solutions used in the bioassays had phytotoxic and allelopathic effects in the development of the test plants.